Ingesting a 12% carbohydrate-electrolyte beverage before each half of a soccer match simulation facilitates retention of passing performance and improves high-intensity running capacity in academy players - Rodriguez-Giustiniani, P.; Rollo, I.; Witard, O. C.; Galloway, S. D. R. (International Journal of Sport Nutrition and Exercise Metabolism, 2019)
This study investigated the influence of ingesting a 12% carbohydrate plus electrolyte (CHO-E) solution providing 60 g of carbohydrate before each half of a 90-min soccer match simulation (SMS) protocol on skill performance, sprint speed, and high-intensity running capacity. Eighteen elite academy (age: 18 ± 2 years) soccer players ingested two 250-ml doses (pre-exercise and at halftime) of a 12% CHO-E solution or electrolyte placebo administered in a double-blind randomized cross-over design. During an indoor (artificial grass pitch) SMS, dribbling, passing, and sprint performance were assessed, and blood was drawn for glucose and lactate analysis. High-intensity running capacity was assessed following the SMS. Dribbling speed/accuracy and sprint speed remained unchanged throughout the SMS. Conversely, passing accuracy for both dominant (mean percentage difference [95% confidence interval, CI]: 9 [3, 15]) and nondominant (mean percentage difference [95% CI]: 13 [6, 20]) feet was better maintained during the SMS on CHO-E (p < .05), with passing speed better maintained in the nondominant foot (mean percentage difference [95% CI]: 5.3 [0.7, 9.9], p = .032). High-intensity running capacity was greater in CHO-E versus placebo (mean percentage difference [95% CI]: 13 [6, 20], p = .010). Capillary blood glucose concentration was higher in CHO-E than placebo at halftime (CHO-E: 5.8 ± 0.5 mM vs. placebo: 4.1 ± 0.4 mM, p = .001) and following the high-intensity running capacity test (CHO-E: 4.9 ± 0.4 mM vs. placebo: 4.3 ± 0.4 mM, p = .001). Ingesting a 12% CHO-E solution before each half of a match can aid in the maintenance of soccer-specific skill performance, particularly on the nondominant foot, and improves subsequent high-intensity running capacity.